1846 Mich. Rev. Stat. 200, § 3 - (:unkn) unknown (My University, 1846)
§ 3. The inhabitants of every township or incorporated village may, at any regular meeting, order that no gunpowder shall be kept in any place within the limits of such township or village, unless the same shall be kept in tight casks or canisters; and that no gunpowder above the quantity of fifty pounds, shall be kept or deposited in any shop, store or other building, or in any ship or vessel, which shall be within the distance of twenty-five rods from any other building, or from any wharf; that no gunpowder above the quantity of twenty-five pounds, shall be kept or deposited in any shop, store or other building, within ten rods of any other building; and that no gunpowder above the quantity of one pound, shall be kept or deposited in any shop, store or other building, within ten rods of any other building, unless the same shall be well secured in copper, tin or brass canisters, holding not exceeding five pounds each, and closely covered with copper, brass or tin covers. § 4. Upon complaint being made on oath to any justice of the peace, by any township or village officer, that he has probable cause to suspect that gunpowder is deposited or kept within the limits of the township or village, contrary to any such order, such justice may issue his warrant, directed to any constable of such township, or the marshal of such village, ordering him to enter any shop, store or other building, or vessel specified in said warrant, and there to make diligent search for the gunpowder suspected to have been deposited or kept as aforesaid, and to make return of his doings to such justice forthwith. § 5. If any person shall commit either of the offences mentioned in the two preceding sections, he shall forfeit a sum not exceeding twenty dollars; but the two preceding sections shall not extend to any manufactory of gunpowder, nor in any case prevent the transportation thereof through any township, or from one part of any township to another part thereof.
Keywords: GUNPOWDER - STORAGE